It’s Raining Lemons! How the COVID-19 Pandemic Reshaped the Association of Jewish Libraries - Margolis, Michelle (Judaica Librarianship, 2022)
The COVID-19 pandemic hit in early 2020, changing expectations and work around the globe. The pandemic forced the Association of Jewish Libraries (AJL) to expedite changes that had been moving along slowly, leading to a completely revamped organization. This article goes through some of the background leading up to COVID-19 and how AJL was already changing and continues to change to meet the needs of its members.